2011
DOI: 10.14797/mdcj-7-3-32
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Aortic Surgery

Abstract: Surgical robotics was first utilized to facilitate neurosurgical biopsies in 1985, and it has since found application in orthopedics, urology, gynecology, and cardiothoracic, general, and vascular surgery. 1 Surgical assistance systems provide intelligent, versatile tools that augment the physician's ability to treat patients by eliminating hand tremor and enabling dexterous operation inside the patient's body. Surgical robotics systems have enabled surgeons to treat otherwise untreatable conditions while also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Such devices have been recently introduced into other surgical subspecialties. 7,10,11,21 However, as noted by Peter Jannetta, one of the first neurosurgeons to document and integrate the microscope into neurosurgery in 1968, "… the hand cannot perform if the eye cannot see…" (personal communication). 25 This may have been why the development of effector robots in neurosurgery has been profoundly limited; specifically, inadequate visualization has been a rate-limiting step.…”
mentioning
confidence: 99%
“…Such devices have been recently introduced into other surgical subspecialties. 7,10,11,21 However, as noted by Peter Jannetta, one of the first neurosurgeons to document and integrate the microscope into neurosurgery in 1968, "… the hand cannot perform if the eye cannot see…" (personal communication). 25 This may have been why the development of effector robots in neurosurgery has been profoundly limited; specifically, inadequate visualization has been a rate-limiting step.…”
mentioning
confidence: 99%
“…Further clinical studies assessing the cost-effectiveness of the endovascular robotic system and the safety and performance in complex clinical cases involving fenestrated stent grafting are necessary to promote the usage of this new technique. 4,12 Although the only functional unit of this new system is in St. Mary's Hospital, Paddington, London, other countries are catching up, with Germany and France due to install a unit soon, and Singapore and Sydney having purchasing plans as well. Most recently, there has been a single case report of robot-assisted fenestrated endovascular aneurysm repair using the Magellan system in a patient.…”
Section: Discussionmentioning
confidence: 99%
“…It was first employed in 1985 for neurosurgical biopsies. 4 Since then, it has been applied in different specialties, especially by gynecologists, urologists and colorectal surgeons operating within the confined space of the pelvis. In recent years, robotic surgery has found applications in vascular surgery, which can potentially reduce the limitations of current endovascular techniques.…”
Section: Clinical Studies On the Feasibility Of Robotic Endovascular Surgerymentioning
confidence: 99%
“…Robotic-assisted systems have developed increasingly over the past 2 decades and are currently applied in various clinical indications in orthopaedics, urology, gynaecology, general and thoracic surgery [ 1 ]. This has allowed surgeons to treat complex clinical syndromes while reducing morbidity and error rates, shortening operating times and improving the overall workflow [ 1 ]. Wisselink et al reported 2002 for the first time on robotic-assisted abdominal aortic surgery (RAAS) treating two patients with robotic-assisted aorto-iliac bypasses [ 2 ].…”
Section: Introductionmentioning
confidence: 99%